Leadership of the Sub-District Head in Preventing the Spread of New Direction Radicalism in Poso Kota Sub-District, Poso District - Ani Susanti; Rivaldi Perdana Bagenda; Nasir Mangangsing (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research investigates the role of sub-district leadership in mitigating the spread of new direction radicalism in Poso District, Poso Regency City. The urgency and significance of this study lie in addressing the escalating radicalism threats in the region. The research method employed is a qualitative approach using a descriptive case study method. Data were collected through in-depth interviews with six informants, field observations, and document analysis. The findings reveal that the instructional leadership style is effective, evidenced by structured communication and community engagement. The consultative leadership style is also successful, involving diverse community and religious groups. Additionally, the participative leadership style supports policy implementation through religious lectures, while the delegation leadership style empowers subordinates to address radicalism prevention. The study recommends enhancing leadership strategies to sustain these efforts